PENGARUH DUKUNGAN SOSIAL KELUARGA TERHADAP COPING STRESS PADA MAHASISWA SEMESTER AKHIR - Maulida Salsabila; Arri Handayani; Padmi Dhyah Yulianti (IKIP Siliwangi, 2026)
Stress coping cannot be separated from the presence of social support. For an individual particularly a college student social support from family members, such as parents, can have a positive influence on that individual’s performance. This study aims to examine the influence of family social support on stress coping among final-semester college students. The study employs a quantitative approach using an ex post facto design and a correlational design through purposive sampling. Data were collected using the Family Social Support Scale and the Stress Coping Scale, both of which met validity and reliability criteria. Anonparametric hypothesis test using Spearman’s Rho correlation revealed a correlation coefficient of 0.559 with a significance level of 0.000. This indicates a significant moderate-level relationship between the two variables, meaning the relationship is quite strong. This positive relationship indicates that the higher the level of family social support received by students from their families, the better their ability to manage stress.